Development of a Phantom for Low Dose Mammography (Medico Legal Update, 2020)
Background/Objectives: Interest in regular mammography has grown as a way for early detection of breast cancer. In this study, we produced a phantom that allows for an evaluation of the image quality of images acquired at different phases using X-rays.Method/Statistical Analysis: To measure the radiation generated during breast cancer diagnosis using X-rays, the X-ray tube system by Varian was used to measure and analyze at a distance of 40 cm under the conditions of 22kVp, 20 mA, and 710mAs. To reduce errors in measurement, imaging of the breasts was done repeatedly for 10 times.Findings: In the absorption image, there were 5.0±0.2 fibers, 4.5 specks and 4.5 masses, making the total 14 which is higher than the 10 required to be officially authorized. In the dispersion and phase differential images, there were 5.5±0.0 fibers, 4.5 specks, and 4.5 masses, making the total 14.5 which is higher than the 10 required to be officially authorized. In addition the image quality was better than that of the absorption image. When a dosimeter was used, the radiation exposure was an average of 2425.85±0.33mR. When the absorbed radiation was measured using a glass dosimeter, it was 1,334±1.82?Gy. This was different from the value converted using the valid radiation.Improvements/Applications: In particular, phase differential imaging is expected to be applied to breast cancer tests where most of the tissue is soft, verification tests for foreign objects and forecasting of the progress in the disease.